The association between glutathione reductase and postmenopausal osteoporosis: a retrospective study - Wang, Jili; Wu, Kaixuan; Chen, Menghan; Li, Xiaoyu; Ban, Saibo; Li, Bingbing; He, Kaiguang; Yang, Huicai; Dai, Qiuqing; Guo, Shaochong; Guo, Ziyuan; Wang, Linyi; et al. (Frontiers in Endocrinology, 2026)
BackgroundOxidative stress is a common pathological condition in postmenopausal osteoporosis. Glutathione reductase, an antioxidant enzyme, plays a critical role in the body’s antioxidant defense system. However, the relationship between glutathione reductase and postmenopausal osteoporosis remains unclear. This study aims to explore the association between glutathione reductase and postmenopausal osteoporosis.MethodsThis study retrospectively analyzed hospitalized postmenopausal women aged over 45 years from China between January 1, 2020, and April 15, 2025. The cases were divided into the osteoporosis group (OP group, T ≤ -2.5) and the non-osteoporosis group (non-OP group, T > -2.5). Initially, independent-samples t-tests were performed to compare differences in continuous variables between the two groups. Subsequently, binary logistic regression was conducted to identify potential predictors, followed by variable selection using the least absolute shrinkage and selection operator (LASSO) regression. The selected variables were then incorporated into a multivariable logistic regression model to determine independent risk factors. Finally, the predictive performance of the model was evaluated using receiver operating characteristic (ROC) curves, concordance index (C-index), calibration curves, and decision curve analysis (DCA).ResultsA total of 401 patients were enrolled in this study, with 149 in the non-OP group and 252 in the OP group. The OP group showed lower BMI, lumbar spine (L1-L4), femoral BMD, and hip BMD compared to the non-OP group (P < 0.05). The OP group had higher age, adenosine deaminase (ADA), and glutathione reductase (GR) levels than the non-OP group (P < 0.05). ROC analysis revealed that the area under the curve for GR was 0.604 (95% CI: 0.556-0.662), with a critical value of 55.8 U/L (P < 0.05). Binary logistic regression and LASSO regression analyses demonstrated that GR ≥ 55.8 U/L was a risk factor for postmenopausal osteoporosis.ConclusionGR are significantly associated with postmenopausal osteoporosis, and GR ≥ 55.8 U/L is an important risk factor for postmenopausal osteoporosis.